Rearrangement of allyl phenyl ether over Al-MCM-41 - Mathew, Nevin T.; Khaire, S.; Mayadevi, S.; Jha, Ratnesh Kumar; Sivasanker, S. (Journal of Catalysis, 2005)
Claisen rearrangement of allyl phenyl ether to o-allylphenol and a dihydrobenzofuran derivative was investigated over MCM-41 with different Si/Al ratios. Higher aluminum content, higher reaction temperatures, and longer run duration favor the formation of the ring compound 2,3-dihydro-2-methyl benzofuran. There is a close relationship between acidity and conversion, which suggests that the reaction occurs inside the large pores of MCM-41. The influence of temperature and catalyst Si/Al ratio on the reaction are examined by kinetic analysis, under the assumption of a first-order consecutive reaction. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: Al-MCM-41; allyl phenyl ether; Claisen rearrangement; Mesoporous material; molecular rearrangement; Solid acids

Claisen rearrangement of allyl phenyl ether over zeolites beta, mordenite and Y - Wagholikar, S. G.; Mayadevi, S.; Jacob, Nalini E.; Sivasanker, S. (Microporous and Mesoporous Materials, 2006)
The Claisen rearrangement of allyl phenyl ether (APE) to o-allylphenol was investigated over zeolites beta (BEA), mordenite (MOR) and Y (FAU) with different Si/Al ratios. Over the zeolite catalysts, the allylphenol cyclized to produce 2,3-dihydro-2-methyl benzofuran. Larger catalyst loading, higher reaction temperatures and longer run duration favored the formation of the ring compound. Conversion was small over MOR and FAU although they possessed higher acidity (as measured by the temperature programmed desorption of ammonia) compared to BEA. Studies using BEA revealed that the nature of the solvent influenced the reaction rate. The order of reactivity in the solvents was, benzene > EDC (1,2-dichloroethane) > toluene > TCE (1, 1,2,2-tetrachloroethane) >> ACN (acetonitrile). The intermediate allylphenol reacted with the aromatic solvents to produce byproducts when benzene and toluene were used as solvents. A kinetic analysis assuming first order series and parallel reactions is presented. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: allyl phenyl ether; allylphenol; Benzofuran; Claisen rearrangement; zeolites

Liquid phase alkylation of phenol with 1-octene over large pore zeolites - Wagholikar, Smita; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2006)
A comparative study is presented of the liquid phase alkylation of phenol with 1-octene over different zeolite catalysts: H-beta (BEA(15)), H-mordenite (MOR(11)) and H-USY (FAU(15)). A wide spectrum of monoalkylated products, identified as isomers of phenyl octyl ether (O-alkylate) and octyl phenol (C-alkylate), was formed in the reaction. The reaction was studied in detail over BEA(15), such studies included the influence of process variables such as temperature, reactant mole ratio, catalyst amount and alkali metal (K) poisoning on its performance in the alkylation reaction. A kinetic analysis of the reaction over BEA(15) was also carried out assuming a second order parallel reaction mechanism. The activity of the different catalysts for the reaction followed the order: BEA(15) > FAU(15) > MOR(11). The poisoning of BEA(15) with potassium resulted in a decrease in the catalyst activity concomitant with a decrease in the number of strong acid centres in the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 1-octene; alkyl phenols; Alkylation; phenol; zeolites

Acylation of anisole with long-chain carboxylic acids over wide pore zeolites - Wagholikar, S. G.; Niphadkar, P. S.; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2007)
The acylation of anisole with long-chain carboxylic acids (hexanoic, octanoic and decanoic) has been studied over three large pore zeolites-beta (BEA), faujasite (FAU) and mordenite (MOR). The acylation of anisole with the long chain acids produced mainly the ketone (4-methoxy phenyl alkyl ketone) and small amounts of the ester (phenyl alkanoate). The results revealed the reaction to be influenced by the type of zeolite and its Si/Al ratio (acidity) besides the chain length (carbon number) of the carboxylic acid. In the acylation of anisole with hexanoic acid, the activity of the zeolites increased with dealumination as it led to the generation of mesopores that resulted in a decrease in diffusion resistance of the zeolites. The reactivity of the acids in the acylation reaction was found to decrease with increase in the carbon number. The experimental data have been fitted into a pseudo first order kinetic model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Anisole; decanoic acid; hexanoic acid; octanoic acid; zeolites

Analysis of a membrane reactor: influence of membrane characteristics and operating conditions - Tanna, Nikunj P.; Mayadevi, S. (International Journal of Chemical Reactor Engineering, 2007)
Modeling of an esterification reaction in a batch pervaporation membrane reactor (PVMR), and an analysis of the PVMR performance under different reaction conditions for different membrane characteristics are presented. Esterification of ethyl alcohol with acetic acid was considered as the model reaction. The PVMR performance for this reaction could be represented by a 2-step series model. The PVMR performance was similar to that of the batch reactor when both the reactors were in the kinetic regime. However, the performance of the PVMR was superior to that of the batch reactor when both were in the intermediate/equilibrium regime of the reaction. In these regions, the PVMR performance was influenced/limited by the membrane flux and selectivity. The analysis showed that the membrane flux affected the PVMR performance in the intermediate region and the membrane selectivity affected the performance in the equilibrium regime. Further, the limitations introduced by a low-flux membrane could be overcome by appropriate selection of the membrane area and that due to poor selectivity could be compensated to a certain extent by adjusting the feed ratio.
Keywords: comparison; Esterification; membrane reactor; performance; pervaporation membrane

Adsorption of fluoride ions by Zn-Al layered double hydroxides - Mandal, Sujata; Mayadevi, S. (Applied Clay Science, 2008)
Zn-Al layered double hydroxides (LDHs) with different molar ratios Zn/Al (0, 0.17, 0.34, 0.97, 3.47, proportional to) were prepared by the co-precipitation of chlorides, characterized and evaluated for their fluoride adsorption at room temperature from aqueous solutions. The fluoride adsorption of the as-synthesized LDHs was influenced by the chemical composition of the LDHs and ZA-11 (Zn/Al = 0.97) had the highest capacity for fluoride adsorption (1.14-4.16 mg/g). The adsorption increased after calcination of the LDH up to 500 degrees C. The equilibrium data were fitted to the Freundlich, Langmuir, and Temkin equations. The kinetics of fluoride adsorption followed the pseudo-second order model. (C) 2007 Elsevier B.V All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Layered double hydroxide

Cellulose supported layered double hydroxides for the adsorption of fluoride from aqueous solution - Mandal, Sujata; Mayadevi, S. (Chemosphere, 2008)
Cellulose supported layered double hydroxides (CSLDHs) were synthesized and tested for adsorption of fluoride in aqueous medium. Three samples of cellulose supported LDHs were synthesized by varying the LDH loading on cellulose. The raw cellulose, unsupported LDH and cellulose supported LDHs were characterized by XRD, SEM and BET surface area. Batch adsorption as well as fixed-bed column experiments were performed for determining the fluoride adsorption characteristics of CSLDHs. The fluoride adsorption properties of CSLDHs were found to be superior to that of reported adsorbents, including activated alumina and carbon nanotubes. Defluoridation capacity of the CSLDHs was 2-4 times higher than that of unsupported LDH. The cellulose supported LDH, CSLDH-50, having an LDH loading of 27% showed maximum fluoride uptake capacity (5.29 mg g(-1) of CSLDH, 25.18 mg g(-1) of LDH) in fixed-bed column study. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; cellulose; Fluoride; Layered double hydroxide

Adsorption of aqueous selenite [Se(IV)] species on synthetic layered double hydroxide materials - Mandal, Sujata; Mayadevi, S.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
{Layered double hydroxide materials (Zn/Al, Mg/Al, Zn/Fe) with varying composition (M(2+):M(3+) molar ratio

Defluoridation of water using as-synthesized Zn/Al/Cl anionic clay adsorbent: equilibrium and regeneration studies - Mandal, Sujata; Mayadevi, S. (Journal of Hazardous Materials, 2009)
Zn/Al/Cl anionic clay has been synthesized by co-precipitation method and applied for adsorption of fluoride in aqueous medium. Equilibrium adsorption data were fitted to Langmuir, Freundlich, Temkin, and Generalized isotherm equations. Thermodynamic parameters like Delta G and Delta H values show the feasibility and exothermic nature of the adsorption process. Influence of solution pH and presence of other anions on fluoride adsorption by the clay has also been studied. Presence of carbonate in water was found to have an adverse effect on fluoride adsorption by the clay. pH(pzc) of the clay has been found to be 8.97. A two-step 1st order kinetic model was used to explain the fluoride adsorption kinetics of the as-synthesized clay. It was possible to regenerate the adsorbent with an aqueous solution of 0.01 M NaOH and the effect of regeneration on fluoride adsorption was reported up to five regeneration cycles. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Isotherm; kinetics; Regeneration

Adsorption of cresols on zinc-aluminium hydroxides - a comparison with zeolite-X - Vijayakumar, J.; Chikkala, Suresh K.; Mandal, Sujata; Mayadevi, S. (Separation Science and Technology, 2011)
Liquid phase adsorption of m-cresol on Zn-Al hydroxide adsorbents with three different Zn/Al molar ratios was studied in different solvents and compared with commercial zeolite 13X. Among the three adsorbents, ZA-16 showed adsorption capacity similar to commercial zeolite 13X. Solvents used for the preparation of m-cresol solution were found to influence the adsorption capacity. The adsorption capacity was maximum for the solution of m-cresol in n-hexane. Conventional Langmuir and Freundlich adsorption isotherm equations were used to explain the adsorption behavior. The kinetics of m-cresol adsorption followed the first-order Lagergren kinetic model. p-Cresol/m-cresol separation factor was the highest when toluene was used as the organic medium.
Keywords: Adsorption; cresol; zeolite; zinc-aluminium hydroxide

Alkylation of anisole with 1-hexene and 1-hexanol over zeolite H-beta - Surse, P. V.; Wagholikar, S.; Mayadevi, S.; Sivasanker, S. (Reaction Kinetics Mechanisms and Catalysis, 2011)
An examination of the kinetics of the alkylation of anisole with 1-hexene and 1-hexanol to produce alkylates over zeolite H-beta is presented. Anisole alkylation is found to occur by a set of parallel reactions when hexene is used as the alkylating agent. When hexyl alcohol is the alkylating agent, the reaction follows a multi-step parallel-series mechanism to form monoalkylates and dihexylether. With 1-hexene, a group of isomeric alkylates, viz., ortho-2-hexyl anisole (2-OHA), ortho-3-hexyl anisole (3-OHA), para-2-hexyl anisole (2-PHA), and para-3-hexyl anisole (3-PHA) was obtained. With hexanol, the olefin (hexene) and dihexyl ether were obtained additionally. The influence of process parameters like temperature, catalyst quantity, and alkylating agent on reaction behavior is reported.
Keywords: Alkylation; Anisole; H-beta; Hexene; Hexyl alcohol

Fluoride contamination of water: origin, health effects and remediation methods - Mandal, Sujata; Mayadevi, S. (Fluoride, 2011)
Fluorine is the 13th most abundant element in the earth?s crust. It exists in trace amounts in ground water all over the world. Drinking water is the primary source through which fluoride enters the human body, especially in regions where fluoride concentrations in groundwater and/or surface water are high. It is estimated that more than 200 million people worldwide depend on drinking water with fluoride concentration exceeding the present World Health Organization (WHO) guideline (Maximum contaminant level of 1.5 mg/l). Fluoride bearing foodstuffs and fumes from burning of coal also significantly contribute to the daily intake of people in some regions. Prolonged consumption of excess fluoride may lead to different types of fluorosis (dental and skeletal) depending on the level and period of exposure. Presence of fluoride in drinking water above permissible level has been related to increased incidence of fluorosis among the people all over the world including China, India, Australia, Mexico, Argentina, Egypt and Kenya. In India, the problem of excessive fluoride in groundwater was first reported in 1937 in the state of Andhra Pradesh. More than 6 million people all over India are known to be seriously affected by fluorosis and another 62 million are exposed to it. The best choice for combating fluorosis is to have alternative source of water with low fluoride level. In absence of alternative source of water, defluoridation of excess fluoride in water is the only option. Different methods are available for defluoridation of water. But the selection of the appropriate method for achieving a sustainable solution to the fluorosis problem is very important. Defluoridation of drinking water by adsorption is the most simple and effective technology that can work in household as well as community level drinking water treatment. It is also the most widely studied method for defluoridation of water, as the fluoride concentration in groundwater is usually very low (10 mg/l). A wide variety of adsorbents have been explored for this purpose. Synthetic layered double hydroxides are comparatively new materials examined for the adsorption of fluorides and they exhibit good fluoride adsorption capacity. A discussion on various defluoridation methods, adsorbents for defluoridation and recent developments are presented in this chapter.

In situ encapsulation of Pt nanoparticles in mesoporous silica: synthesis, characterisation and effect of particle size on CO oxidation - Prashar, Atul K.; Mayadevi, S.; Rajamohanan, P. R.; Devi, R. Nandini (Applied Catalysis A-General, 2011)
Pt nanoparticles of narrow size distribution and average particle size of 4.4 nm are isolated exclusively inside SBA-12 mesoporous silica by a novel in situ method. The interaction of Pt precursor with surfactant-polymer composite micelle is followed by NMR and UV studies. The final Pt incorporated silica material is characterised by XRD, TEM and N(2) adsorption. The mesoporous nature of the silica is found to be intact after Pt incorporation without any pore blockage. CO oxidation activity of this material is compared with that of mesoporous silica incorporating different sizes of Pt viz., 1.8, 3.6 and 8 nm. Activation energies of CO oxidation for all these materials are calculated by a simple differential method based on first principles. A comparison of activation energies and single site yields reveals that these parameters are distinguishably less in catalyst containing 1.8 nm Pt nanoparticles but more or less same in catalysts containing 3.6, 4.4 and 8 nm Pt nanoparticles. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; In situ synthesis; Mesoporous silica; Pt nanoparticle

Alginate and hydrotalcite-like anionic clay composite systems: synthesis, characterization and application studies - Mandal, Sujata; Patil, Varsha S.; Mayadevi, S. (Microporous and Mesoporous Materials, 2012)
Hydrotalcite-like anionic clays (Zn/Al and Mg/Al) were intercalated with sodium alginate to form organic-inorganic composite adsorbents for water treatment applications. The synthesized composites were characterized using different characterization techniques viz. XRD, DRIFTS, SEM and surface area/porosity analysis. The adsorption potential of the alginate-clay composites was examined for removal of fluoride ions and Orange II dye from water by adsorption. Our studies revealed that these composites had high adsorption capacity for the adsorption of fluoride and Orange II dye from aqueous solutions. The adsorption capacity of the composites was considerably higher than that of either alginate or clay, used individually. The results indicated that these materials might be useful sorbents for groundwater purification/effluent treatment. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Alginate; Anionic clay; Composite; Fluoride; Orange II dye

Effect of particle size on selective hydrogenation of cinnamaldehyde by Pt encapsulated in mesoporous silica - Prashar, Atul K.; Mayadevi, S.; Devi, R. Nandini (Catalysis Communications, 2012)
Pt nanoparticles of various sizes, viz. 8. 4.9, 3.6 and 1.8 nm were encapsulated in 2D hexagonal mesoporous silica by in-situ synthesis as well as post synthetic modifications so that the final catalyst composition was <= 1 wt.% Pt/SiO2. A kinetic analysis of the effect of particle size on selective hydrogenation of cinnamaldehyde was carried out on these catalysts. It was found that the materials, even at such low loading of Pt, were very active for the hydrogenation and selective for the desired product, cinnamyl alcohol. Among the different particle sizes, selectivity was found to be the highest on 8 nm particles. Kinetic analysis shows that the reaction follows a consecutive reaction pathway. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: alpha; beta-Unsaturated aldehydes; Cinnamaldehyde hydrogenation; Kinetic analysis; Mesoporous silica; Pt nanoparticles; Selective hydrogenation

Reactions in supercritical carbon dioxide - Mayadevi, S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Use of conventional organic solvents often leads to the formation of hazardous waste, the disposal of which is a matter of environmental concern. Carbon dioxide is considered to be a green reaction medium and a good replacement for conventional organic solvents as it is benign and leads to elimination/reduction of hazardous wastes. Use of CO2 at near/above critical conditions has several additional advantages as the reactions can be pressure-tuned to eliminate transport resistance, increase solvent power and heat capacity. Hence, there has been considerable interest in the use of supercritical carbon dioxide as either a replacement of conventional organic solvent or as a co-solvent in reactions. Herein, recent developmenst in this area during the last decade is reviewed, specifically in gas-liquid (organic hydrogenation, hydroformylation and oxidation) and liquid-liquid (carbon-carbon coupling, alkylation, acetylation, esterification) reactions.
Keywords: Alkylation; Carbon dioxide; Hydroformylation; Hydrogenation; Oxidation; Supercritical carbon dioxide

Trends towards zero discharge of distillery effluents - Gokarn, A. N.; Pande, Anita R.; Mayadevi, S. (Trends towards zero discharge of distillery effluents, 2012)
In the present paper we have described briefly a customer friendly process for the treatment of distillery effluent to obtain colourless water.In order to bring about improvement of cost factor, our developmental efforts towards cheaper and efficient adsorbents have been elucidated. Further improvement of its cost factor could be achieved by enhancing the colour removal ability of the adsorbent (activecharcoal) with small quantities of oxidizing agents (in ppm level). Recent developments towards obtaining valueadded products from spent wash using various methodologies and techniques have been reviewed with a view to encourage technocrats and entrepreneurs to take lead in this challenging and economically attractive endeavor

Preparation and characterization of porous fly ash/NiFe2O4 composite: promising adsorbent for the removal of congo red dye from aqueous solution - Sonar, Shilpa K.; Niphadkar, Prashant S.; Mayadevi, S.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2014)
A series of fly ash/NiFe2O4 composites were prepared using fly ash and aqueous solutions of Ni, Fe nitrate salts and NaOH by co-precipitation followed by calcination method. The % mass ratio of fly ash: NiFe2O4 was varied in the range of 0:100 to 100:0. Samples were characterized by powder XRD, SEM, FTIR and N-2 adsorption-desorption measurements. These samples were further evaluated for their adsorptive performance in removal of Congo red (CR) dye from an aqueous solution. In all the composites, spinel nickel ferrite phase was found to be capable to get anchored with the fly ash surface and exhibited more crystalline nature as compared to pure NiFe2O4 phase. The BET surface area and porous character of the composite were found to increase with the decrease in the contribution of the fly ash, reach to maximum and then decreases on further decrease in fly ash. The composite having % mass ratio of fly ash: NiFe2O4 = 50:50 exhibited maximum CR adsorption from the aqueous solution on account of the higher BET surface area, more porous character, favorable condition for diffusion of dye molecules and combined effect of chemisorption and physisorption. Under optimum conditions, it has shown the recyclability with adsorption capacity of the magnitude 23.33 mg g(-1), which is much higher than individual fly ash, NiFe2O4 and other composites. The sorption data provided good fit with pseudo-second order kinetic model. The analyses of the adsorption data indicated that, the Langmuir model provides better correlation with the experimental data. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Composite material; Electron microscopy (SEM); Inorganic compounds; powder diffraction; Precipitation

Sorption of metaldehyde using granular activated carbon - Salvestrini, S.; Vanore, P.; Bogush, A.; Mayadevi, S.; Campos, L. C. (Journal of Water Reuse and Desalination, 2017)
In this work, the ability of granular activated carbon (GAC) to sorb metaldehyde was evaluated. The kinetic data could be described by an intra-particle diffusion model, which indicated that the porosity of the sorbent strongly influenced the rate of sorption. The analysis of the equilibrium sorption data revealed that ionic strength and temperature did not play any significant role in the metaldehyde uptake. The sorption isotherms were successfully predicted by the Freundlich model. The GAC used in this paper exhibited a higher affinity and sorption capacity for metaldehyde with respect to other GACs studied in previous works, probably as a result of its higher specific surface area and high point of zero charge.
Keywords: Degradation; Diffusion-controlled Sorption; Environmental Pollution; Granular Activated Carbon; Metaldehyde; Sorption Adsorption

Synthesis of biomass waste derived activated carbon-NBR composites for automobile application - Jadhav, A.; Mohanraj, G.T.; Gokarn, A.; Mayadevi, S. (Chemistry and Chemical Technology, 2018)
This paper reports on usability of activated carbon obtained from areca nut shell, coconut shell, and coconut leaves as a filler to prepare NBR based composite for automobile based application. The carbon was activated by phosphoric acid (H3PO4) as dehydrating agent. The stoichiometric ratio of biomass and phosphoric acid was found to be 3:1 for the batch size of 300 g. As compared to commercially available carbon filler, the activated carbon derived from biomass waste responded better to the petrol swelling test. Among three biomass waste sources, namely, areca nut shell, coconut shell, and coconut leaves, activated carbon derived from coconut shell was appeared to be the best for percent swelling and percent deviation in hardness. The results obtained are confirmed by proximate analysis.
Keywords: activated carbon; composites; hardness; NBR; Phosphoric acid

Variations in activity of Ru/TiO(2 )and Ru/Al2O3 catalysts for CO2 hydrogenation: an investigation by in-situ infrared spectroscopy studies - Dongapure, Pavan; Bagchi, Sayan; Mayadevi, S.; Devi, R. Nandini (Molecular Catalysis, 2020)
CO2 hydrogenation to methane, an important reaction strategically and also for value adding to CO2, is investigated on two different catalysts, Ru supported on alumina as well as titania to understand better low temperature activity of Ru/TiO2 catalyst. In-situ infrared studies are carried out in three different steps, viz., (i) CO2 adsorption on fully reduced catalyst (ii) reaction of these adsorbed species with gaseous H-2 and (iii) under co-feed of CO2 and H-2, at different temperatures. On Ru/Al2O3 catalyst, CO2 reacts with hydroxyls on the support surface to form carbonate and adsorbs reductively on metal as CO. Further reduction to formate and methyl species occurs on reaction with H. Small concentration of the reactive intermediate formyl forms only at high temperatures. Whereas, bare TiO2 itself seems capable of reductive adsorption of CO2 as formate indicating enhanced reducibility of titania based catalyst. Formyl groups are observed at low temperatures in Ru/TiO2 in step (ii), which further forms methyl and gaseous methane at much lower temperatures when compared to alumina catalyst. Highly reactive CO species loosely bound to metal-support interface observed at high temperatures, which is not present on Ru/Al2O3 catalyst also makes this catalyst superior. In comparison, linearly bound CO seen in alumina catalyst is not as reactive.
Keywords: CO2 hydrogenation; In-situ infra red spectroscopy; Ru/Al2O3; Ru/TiO2

Synthetic layered double hydroxide on biodegradable support: an efficient adsorbent for defluoridation of water - Mayadevi, S.; Kirandas, M. D.; Manilal, A. M.; Roshini, N.; Mandal, Sujata (Indian Journal of Chemical Technology, 2024)
Fluoride concentrations in drinking water above permissible levels and incidences of fluorosis among people have been reported from many parts of the world including India. Low-cost and biodegradable adsorbents are the preferred choice for the removal of fluoride from an aqueous medium. In the present study, zinc-aluminium layered double hydroxide (LDH) supported on sugarcane bagasse (raw and acid-treated) has been synthesized, characterized, and investigated for the defluoridation of water. The SEM micrographs of the supported adsorbents show good dispersion of the LDH particles on the support material. The defluoridation capacity of the LDH is enhanced by supporting it on bagasse. The adsorption capacity of supported adsorbents increased by 3-fold than the unsupported LDH adsorbent. The adsorption data have been well fitted to the Freundlich isotherm model indicating physical and multi-layer adsorption. The maximum fluoride adsorption capacity has been found to be 8.85 mg/g with 76.3% fluoride removal when the initial fluoride concentration is 11-12 mg/L. The pseudo-second-order kinetic model has been found suitable to explain the fluoride adsorption kinetics on the supported LDH adsorbents. The present study reveals that the bagasse-supported LDH adsorbent has a high potential for defluoridation of water.
Keywords: adsorption kinetics; Fluoride adsorption; Layered double hydroxide; Sugarcane bagasse